Autoavaliação do Centro de Ensino e Aprendizagem em Rede – CEAR – UEG: constituição da cultura institucional avaliativa - Almeida, Aline (2022)
This dissertation has as its research object the culture of self-assessment of the Network Teaching and Learning Center (CEAR) in the period from 2015 to 2020 and its relationship with the current administrative reform of the State University of Goiás (UEG). The evaluative culture is understood as part of the self-evaluative processes of an institution and that is in accordance with the context in which it is inserted, in addition to a simply bureaucratic step, which should allow reflections on its mission and requirements of quality education. The trajectory and culture of self-assessment is investigated, and how this culture has been constituted at CEAR, in addition to the relationship it establishes with the current administrative reform of the UEG. To better understand the meanings and concepts of self-assessment in higher education and to support the research, authors such as Dias Sobrinho (2003; 2008; 2010; 2013), Campos (2019) and Cruz e Lima (2019), and others, support the debates posed by the research. Understanding that CEAR offers graduation in the distance education modality, it is also essential to know the particularities that the field of study presents with the increasing increase of graduation courses in this modality. The research is qualitative and uses the case study as a type of research. Data collection was carried out through a literature review and research of documents of norms and guidelines on the institutional evaluation of higher education, in addition to other documents about the self-evaluation process found on the institution's website, such as the reports that bring the results of self-assessment processes. Finally, field research was arried out, through semi-structured interviews with those involved in the self-assessment stages and representatives of different segments: managers, teachers, administrative technicians and students. Finally, field research was carried out, through previously structured interviews with those involved in the self-assessment stages and representatives of different segments: managers, teachers, administrative technicians and students. The research is relevant because previous studies show the importance of self- assessment processes in Higher Education Institutions (IES) and the positive impacts that this process of building an evaluative culture causes in them. The analyzes point to different views on the institutional assessment of the UEG, the self-assessment at CEAR and its dissemination, according to the research participants. While representatives of management positions understand the importance of the self-assessment process and its consequences, representatives of technicians and students are unaware of the process. The data also show that, in the construction of self-assessment reports, there are no specificities of the distance modality. Another point of analysis was the 2020 administrative reform, which made it impossible for a member of CEAR to be represented in the UEG's Own Assessment Commission (CPA), due to the cuts in the center's management and coordination positions, resulting from a mass dismissal promoted by the government of the State of Goiás in 2019. These data point to the deconstruction of the evaluative culture at CEAR, which lost its representation in the UEG evaluative process, which made the discussions of the distance modality and its performance in the institution unfeasible. The analysis of data and references allow us to conclude that the constitution of an evaluative culture at CEAR-UEG is still fragile and has not been successful.